CRISPR/dCas9-mediated cell differentiation. (September 2018) - Gong, Jing; Tang, Ding; Leong, Kam
Abstract: Directed differentiation is a critical tool for regenerative medicine as well as bioengineering. While conventional methods for cell state manipulation rely on separate viral vectors for each transcription factor and occasionally repeated transfections for long-term overexpression, CRISPR/dCas9-mediated endogenous activation may offer a simpler and potentially more attractive alternative. By combining the DNA-binding domain of an inactive Cas9 protein with the catalytic domain of epigenetic or transcriptional effectors, endogenous gene expression or repression can be achieved at a specific locus with the addition of a guide RNA. Here, we outline the toolset built on these dCas9 fusion proteins and its application to generate target cells with directed differentiation from stem cells or direct conversion from adult cells. Further, we look toward the potential role that dCas9 can play in the more accurate recapitulation of cell states and efficient manipulation for applications in regenerative medicine and disease modeling.